Network security evaluation using the NSA IEM - Rogers, Russ; Cunningham, Bryan, JD (Syngress ; Distributed by O'Reilly Media in the United States and Canada, 2005)
Network Security Evaluation provides a methodology for conducting technical security evaluations of all the critical components of a target network. The book describes how the methodology evolved and how to define the proper scope of an evaluation, including the consideration of legal issues that may arise during the evaluation. More detailed information is given in later chapters about the core technical processes that need to occur to ensure a comprehensive understanding of the networks security posture. Ten baseline areas for evaluation are covered in detail. The tools and examples detailed within this book include both Freeware and Commercial tools that provide a detailed analysis of security vulnerabilities on the target network. The book ends with guidance on the creation of customer roadmaps to better security and recommendations on the format and delivery of the final report. * There is no other book currently on the market that covers the National Security Agency's recommended methodology for conducting technical security evaluations * The authors are well known in the industry for their work in developing and deploying network security evaluations using the NSA IEM * The authors also developed the NSA's training class on this methodology.